Analysis of Factors Caused by Non-Ownership of Waste Water Drains (Spal) and Efforts to Approach Environmental Health Aspects to Increase Spal Ownership in Communities of Tigapanah District in 2023 - Susanti Br Perangin-angin; Haesti Sembiring; Nelson Tanjung (MultiTech Publisher, 2023)
This type of research is qualitative with an exploratory study approach to get an overview of the factors that cause people not to have SPALs so that efforts can be made to overcome them, in the form of education and making environmentally friendly SPALs. Based on demographic data regarding the factors causing the lack of ownership of waste water disposal channels (SPAL) and efforts to approach environmental health aspects to increase SPAL ownership in the Tigapanah sub-district community in 2023, namely the most dominant age group is 41-60 years old, 175 people (49%) and the most aged 10-20 years as many as 5 people (1.4%), the most dominant occupation is farmers as many as 247 people (69.2), the most dominant education is middle school - high school as many as 232 people (65%), at least D1 education there were 31 people (8.7%), the most addresses were in Seberaya village as many as 79 (22.1%), and the fewest addresses were in Aji Julu village as many as 6 people (1.7%). The number of household residents who predominantly live in 1 house with 4 people or more is 186 people (52.1%) while 1 -3 people are 171 people (47.9).